Pengaplikasian P5 Kurikulum Merdeka Pada Mata Pelajaran Yang Ada Di SD Pembangunan Laboratorium UNP - Kurnia Nur Aini; Sarah Nur Salam; Yudha Maya Septiana (Universitas Maritim AMNI Semarang, 2024)
This research reveals the implementation of the Pancasila Student Profile Strengthening Project (P5) at SD Pembangunan Laboratorium UNP with the aim of understanding the implementation of P5 in the school. The research method used is qualitative with data collection through observation and interviews. The results showed that P5 has been implemented since the beginning of the semester of 2023, with activities taking place every three months. Full participation of students and the role of educator mentors are seen in the implementation of P5. P5 is themed